SMART PARENT: Independent Parenting Strategy through Workshop of Parenting for Single Parents - syaifullah, syaifullah; Susanto, Irman; Nurhijriah, Nurhijriah (Abdi Masyarakat, 2025)
The SMART PARENT program aims to enhance parenting skills and reduce stress among single parents in Kelurahan Ule. The main issues faced by single parents include the dual role as breadwinners and primary caregivers, leading to emotional and social stress. In addition, low financial literacy and limited knowledge of modern parenting techniques exacerbate the situation. This program was implemented through a parenting workshop that integrated evidence-based parenting training, psychosocial support, and economic empowerment through financial literacy training and microenterprise skills. The results of the training showed a 23.4% improvement in participants’ knowledge of positive parenting, a 26% reduction in stress, and an average income increase of 32.7%. The program also succeeded in creating a supportive community, reducing social isolation, and increasing solidarity among participants. This program not only improved parenting quality but also contributed to the social and economic well-being of families, supporting the achievement of relevant SDGs related to poverty and gender equality.